Penyerahan Penne Anreang dalam Tradisi Perkawinan Adat Bugis Parepare : Kajian Gender dan Hukum Islam - Sudirman, Muh.; Mustaring, Mustaring (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2022)
The purpose of this research is to examine the philosophical meaning of the In Penne Anreang tradition in Bugis Parepare traditional marriages in relation to gender and Islamic law. To reveal the deep meaning of the object being studied, this research is included in the type of ethnographic research with a descriptive qualitative approach. Data obtained through interviews and documentation. The results of the understanding obtained that the meaning of the message contained in several symbols used in the tradition of surrendering penne anreang in Bugis Parepare traditional marriages contains hopes and messages, therefore it needs to be preserved. The philosophy contained in the symbols of surrender of penne anreang in Bugis Parepare traditional marriages is in line with basic principles in Islamic teachings and includes al-'urf al-sah, namely habits that are carried out in society and do not conflict with the principles of Islamic teachings, do not eliminate benefit and does not bring harm to the perpetrators. Judging from the benefit of being at the tahsniyat level, namely knowing the level of needs which if not met, it does not threaten the existence of one of the maqāshid al syariyyah (objectives of Islamic law) and does not cause difficulties.